Optimization of fermentation medium for spore production of Paenibacillus polymyxa IN937a and its antifungal activity - Trung Hieu, Pham; Dai Lam, Tran; The Tam, Le; Thi Thoa, Vu; Thi Phuong Thao, Nguyen; Tu Cuong, Ho; Dinh Hoang, Vu; Dang Quang, Le (Vietnam Journal of Biotechnology, 2022)
In this study, we optimized the fermentation medium for spore production of Paenibacillus polymyxa IN937a. Seven factors including molasses, glucose, magnesium sulfate, potassium pyrophosphate, yeast extract, zinc sulfate, and ammonium sulfate are selected as the basis for the screening of factors affecting the spore production of P. polymyxa IN937a by the Plackett-Burman experiment. Based on the analysis of the Plackett-Burman matrix, the result showed that yeast extract, molasses, and ammonium sulfate were the three main impact factors (P < 0.05), which affected the yield of P. polymyxa IN937a spores. Then, the optimum combination of the three factors was subsequently optimized by the response surface methodology (RSM) using Box-Behnken design to increase the spore production in P. polymyxa IN937a fermentation. The obtained results by RSM predicted that maximum spore density of P. polymyxa IN937a was 6.606×109 spore/mL after 48 hours of the experiment when the appropriate medium for the spore production of P. polymyxa IN937a included yeast extract 14.44 g/L, molasses 19.14 g/L, and ammonium sulfate 0.20 g/L. In addition, the antifungal activity of P. polymyxa IN937a was also tested in this study. The preliminary results of in vitro antifungal activity indicated that P. polymyxa IN937a had a good inhibition on the growth of two phytopathogenic fungal strains Sclerotium rolfsii and Rhizoctonia solani. These results could be used for further research on the fermentation of P. polymyxa IN937a on a pilot scale to obtain the optimal number of spores for use in the development of biological crop protection products.